196 Clinical symptoms and condition-specific health-related quality of life impairments in amateur athletes following return-to-activity after sport-related concussion: a prospective, matched-cohort study. (3rd March 2020) - Büttner, Fionn; Howell, David; Doherty, Cailbhe; Blake, Catherine; Ryan, John; Delahunt, Eamonn
Abstract : Background: An understanding of the natural history of sport-related concussion is required to: identify concussed athletes at high risk of prolonged recovery, initiate targeted individualized management, and prevent poor clinical outcomes. Health-related quality of life (HRQoL) is a multi-faceted concept that facilitates the longitudinal assessment of patients' health perceptions and offers reliable insights into individually experienced functional limitations. Objective: To investigate the recovery of athlete-reported symptoms and condition-specific HRQoL at three clinical assessment time-points following sport-related concussion. We hypothesized that condition-specific HRQoL would be significantly different, on average, in concussed athletes only within 1-week following injury, when compared to a matched, control group. Design: Prospective, matched-cohort study. Setting: University human movement laboratory. Participants: We recruited adult amateur athletes who were diagnosed with a sport-related concussion by emergency department physicians. We also recruited sex-, age-, and activity-matched control participants. Assessment: Concussed participants were prospectively assessed at three time-points following injury; 1) within one week following sport-related concussion; 2) upon medical clearance to return-to-activity, and; 3) two weeks following return-to-activity. Control participants were assessed at matched time-points. Main outcome measurements: At each time-point, participants completed five HRQoL patient-reported outcome measures to evaluate the impact of clinical symptoms on their functional limitations. Results: Fifty concussed and fifty matched control participants completed the study protocol. Upon return-to-activity, a significantly greater proportion of concussed participants exhibited clinically impaired headache, neck pain, and dizziness HRQoL scores compared to control participants. Two weeks after return-to-activity, there was still a significantly greater proportion of concussed athletes with clinically-impaired headache (x 2 (1)=9.0; OR=4.4 (95%CI=1.5–15.2); p=0.003) and dizziness (x 2 (1)=9.5; OR=13.5 (95%CI=1.8–604.9); p=0.006) HRQoL scores. Conclusions: A small proportion of concussed athletes exhibited persistent headache and dizziness HRQoL scores beyond return-to-activity following sport-related concussion. This sub-cohort may benefit from early, targeted interventions to reduce the risk of poor clinical outcomes.